2012
DOI: 10.1039/c2jm32809g
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic investigation of mechanochromic luminescent organoboron materials

Abstract: Mechanochromic luminescence (ML) refers to the luminescence color and/or intensity change of solidstate materials induced by mechanical perturbations. For organic molecular solids, this phenomenon is related to the specific packing modes and orientations of individual fluorophores, which could give rise to different excited-state interactions. The molecular solids of difluoroboron dibenzoylmethane (BF 2 dbm) derivatives were previously found to exhibit reversible ML at room temperature and are promising as sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 64 publications
8
87
0
Order By: Relevance
“…3 All lifetimes were fit to multi-exponential decays as is typical for this family of solid-state dyes. 1,6,9 Such behavior is indicative of either excimer or ground state dimer formation, perhaps H-aggregates as proposed by Zhang et al [10][11][12][13] The H, F, Cl, and Br dyes all showed substantial increases in their pre-exponential weighted lifetimes (Table S2.2 Appendix A) after smearing while the I dye actually showed a slight decrease in this value. This may be attributed to increased intersystem crossing from S 1 to T 1 .…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…3 All lifetimes were fit to multi-exponential decays as is typical for this family of solid-state dyes. 1,6,9 Such behavior is indicative of either excimer or ground state dimer formation, perhaps H-aggregates as proposed by Zhang et al [10][11][12][13] The H, F, Cl, and Br dyes all showed substantial increases in their pre-exponential weighted lifetimes (Table S2.2 Appendix A) after smearing while the I dye actually showed a slight decrease in this value. This may be attributed to increased intersystem crossing from S 1 to T 1 .…”
mentioning
confidence: 80%
“…The blue-shifted emission observed in C 12 H 25 powders has been previously ascribed to the steric hindrance of the C 12 H 25 chain limiting dye-dye interactions that red shift emission. 13 In methoxysubstituted analogues, dye-dye interactions such as π-stacking and longer range effects that would red shift emission are more probable since the β-diketonate cores are closer together, undiluted by packed alkyl chain domains. 13,15 This result is analogous to a study performed by Nguyen et al wherein BF 2 dbm derivatives with long alkoxyl chains exhibited more blue-shifted solid-state emissions compared to shorter chain derivatives.…”
Section: Pristine Powdersmentioning
confidence: 99%
See 3 more Smart Citations